Global Analytical Tools on Trade (GATT) - International Food Policy Research Institute (International Food Policy Research Institute, 1990)
The Global Analytical Tools on Trade (GATT) provides a detailed picture of trade and trade policy indicators by category of products at the country level. Displaying indicators on maps allows for an easy comparison of trade and trade policies country profiles. Using the GATT tools users (researchers, students, policy analysts, journalists) can browse a large set of indicators on interactive maps and can export the underlying data in a table or the maps in picture format to include them in their own work.